Strengthening Islamic Philanthropy for Community Empowerment through Muhammadiyah and Nahdlatul Ulama Initiatives in West Java - Achmad, Willya (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2024)
Many communities are still trapped in poverty, with limited access to resources and economic opportunities. Certain community groups, especially in remote areas, often do not have equal access to education, health, and public services. The problems of poverty and social welfare today can be overcome through Islamic philanthropy which includes zakat, infaq, and sedekah. This study aims to analyze the role of Islamic philanthropy in community empowerment through Muhammadiyah and Nahdlatul Ulama institutions in West Java. This study uses a qualitative approach with a case study method. Data are sourced from articles and journals discussing Islamic philanthropy, including case studies relevant to the West Java context. The results show that Muhammadiyah and Nahdlatul Ulama (NU) play an important role in social philanthropy in Indonesia, each with an approach that focuses on health, education, and community empowerment. Both organizations have a significant impact on community empowerment, with their contributions including poverty alleviation, increasing access to education, and improving health conditions. Challenges and limitations in Muhammadiyah and NU philanthropic efforts include the lack of efficiency in fund management, low community participation, and difficulty in reaching vulnerable groups. In addition, both organizations often face challenges in terms of coordination and collaboration between institutions, which can hinder their philanthropic impact. It is hoped that further research can improve the impact of Islamic philanthropy on society.